Communication Skills of Autistic Children at the Karya Tulus Special School in Medan City for Social Interaction - Rizky Chairunnisyah; Sori Monang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The birth of a child in family life is a real source of happiness for a married couple. The best hope is directed at the growth and development of children. However, there are several births of children that are not the family's expectations. Children with neurological disorders (neurodevelopmental disorders). Autism is one of the children who have a neurological disorder which is directed at sensory integration disorders. Where this results in a lack of nerve function, one of which is in communicating. This study aims to determine the communication skills of autistic children in social interaction at Special Schools (SLB)-C Karya Tulus, Medan City. The method used is a type of qualitative research method with the "Purposive Sampling" technique, namely the sample selection technique according to the researcher. There are 3 subjects with autistic children with the initials KM, S, BS and there were two additional informants namely Veronika Ginting and Masdah Br. Matanari as the class teacher. Data collection techniques were carried out using observation and interview methods as well as documentation studies. As a basis, this research uses Herbert Blumer's Symbolic Interaction theory. The results showed that only one out of three subjects could be said to be capable of social interaction. The form of communication that KM does when interacting socially is in the form of two-way communication from the researcher to the subject. KM can read, write, count, and execute commands. While S, and BS are subjects who both have deficiencies in social interaction. Eye contact is unstable and less cooperative in social interaction, especially in answering researcher's questions.